Malay characters in Lloyd Fernando’s Green is the colour - Ramlan, Wan Nur Madiha (International Islamic University Malaysia, 2014)
This essay focuses on how members of the Malay community are characterised in Lloyd Fernando‟s Green is the Colour (1993) by highlighting the complexities and nuances surrounding Malay identity. Fernando‟s characterisation of Malays puts focus on discourses of identity and belonging that continue to dominate imaginaries on personal and national levels. By putting the 1969 Sino-Malay Race Riots and the Islamic Revivalism of the 1980s into context, Fernando enables a discussion not only on the many aspects of being Malay, but at the same time address how these many facets of “Malay” identity inform and are informed by the Malaysian socio-political landscape.